Computer-Aided Screening of the Binding Affinities of Some Anti-Diabetic Ligands Obtained from Annona muricata Linn. (Soursop) and their Derivatives against Alpha-glucosidase - Kingsley Chukwunonso Agu (Elsevier, 2022)
Background: Delaying glucose absorption into the blood - post-prandial - after food intake can play a major ameliorative role in the lifestyle and economic advantage of diabetic (DM) patients, making type 2 diabetes (T2DM), unlike type 1 (T1DM), considerably more, manageable, curable, and preventable. Identifying plant-based lead compounds that will offer much more precise and potent anti-DM activities, with lesser side effects is beneficial. Method: In this experiment, virtual investigations were done to study the binding properties of some phytoconstituents of Annona muricata (annonaceous acetogenin and flavonoids) and their analogues, against α-glucosidase, to identify possible variations of binding affinities with changes in side-chain moieties, modification of carbon-skeleton through increased cyclisation, side-chain hydroxylation, steric-distortion of the beta-lactone ring of acetogenins, the effect of the introduction of glycoside side-chain moiety. Results: The acetogenins and naringenin analogues, pentahydroxy flavanone (-10.40 Kcal/mole), floro-tetrahydroxyflavan (-10.20 Kcal/mole), tetrahydroxyflavan (-10.00 Kcal/mole), naringenin (-09.40 Kcal/mole),  naringenin analogue (-09.20 Kcal/mole), as well as, 15 - acetyl - guanacone - 3 (-9.20 Kcal/mole), recorded relatively high binding energies, suggesting that they bonded better as inhibitors, compared to the other compounds, and the standards, metformin (-4.60 Kcal/mole), except acarbose (-9.70 Kcal/mole). The observed major amino acid residues targeted for bonding by the ligands ranged between Arg422, Asn424, Tyr425, and Arg426. Conclusion: It was, however, observed that the addition of glycoside moiety, increasing the number of hydroxyl groups and rings within the carbon-carbon chain (which ultimately generates constitutional isomers) of α-glucosidase inhibitors could further increase their inhibitory potentials against their binding site.